Sea ice conditions and navigability through the Northeast Passage in the past 40 years based on remote-sensing data - Miao Yu; Peng Lu; Zhiyuan Li; Zhijun Li; Qingkai Wang; Xiaowei Cao; Xiaodong Chen (International Journal of Digital Earth, 2021)
Sea ice conditions and navigability along four typical routes of the Northeast Passage (NEP) are analysed using remote-sensing data from 1979 to 2019. The influence of air temperature (Tair) and surface wind on the sea ice concentration (SIC) and the navigability of routes is determined. It is found that the annually averaged SICs of the different routes have decreased over the past 41 years. The fastest rate of decrease occurred in the Kara Sea (∼−1% per year), while the slowest rates of decrease occurred in the Laptev/East Siberian Sea (∼−0.42% per year). The number of navigable days for the Kara Sea has become ∼1–2 months longer than the Laptev/East Siberian Sea route as a result. The effect of Tair on SIC, quantified by ΔSIC/ΔTair in the routes through the eastern Kara Sea and Laptev/East Siberian Sea in 2010s was ∼−0.04/°C, two to three times that seen during the 1980s. Air temperature is becoming a significant driving force of melting ice in these routes. Surface winds are also a crucial factor for the navigability of the Vilkitsky Strait and Long Strait, as they drive ice drift, and affect the navigability of the Kara Strait by introducing warm air.